State reform and the articulation of the productive sectors - Quintanilla Alarcón, Guillermo (2015)
This research has three purposes. First, prove the existence of weak links between business networks and production chain and the sectors of mining and processing activities. Second, support the need for public policy articulation productive sector, new type as a prerequisite for sustained economic growth through job creation (inclusion) where exploitation, production and processing are crawler’s condition. Third, present the broad outlines of this policy of promoting joint to productivity and competitiveness the national productive apparatus. Finally, an approach to a draft law and public policy articulating the productive sectors that can be implemented in the medium or long term and to enable the State to guide economic development of the country in an articulated manner via their public sectors is forcing productive in the comprehensive reform of State involving central level, a progressive reduction of ministries and public institutions, which in turn have an impact on the most efficient organization of regional and local governments, so that they can fulfill their role as the drivers of development of the country.